Effects of In-Service Teacher Training on Students’ Psychological Development at Secondary Level - Faryal Arshad,; Kayani, Almas Ikram; Qaiser Suleman, (JIE, 2023)
The purpose of the study was to examine the effects of in-service teacher training programmes on students’ psychological development at the secondary level in Rawalpindi District and Islamabad. The objectives of the study were; to identify the factors contributing to students’ psychological development; to analyze the effects of in-service teacher training programmes on the students’ psychological development; and to find out the relationship between in-service teacher training programmes and the most crucial psychological factors affecting the overall development of students. The research was descriptive and quantitative in nature. A sample of total 221 teachers and 672 students from Rawalpindi District and Islamabad was selected through stratified random sampling technique. Two self-developed questionnaires were used for gathering information from the participants. Statistical tools i.e., mean, standard deviation and chi-square test were employed for data analysis. The findings revealed that in-service teacher training programmes have a positive effect on the psychological development of students. There is a significant relationship between in-service teacher training programmes and the most crucial psychological factors effecting the overall development of the students. Based on findings, it was recommended that teachers may be trained professionally to provide better quality of education to students according to their psychological needs.